(untitled) (REVISTA NODO, 2022)
Can aesthetics play a privileged role within today’s encyclopedia of knowledge? The present contribution is centered around this question, which calls into question the very status of the discipline, which has always oscillated between analysis of sensible knowledge and of the work of art/beauty. Through a series of insights elaborated by authors such as Raymond Ruyer, Alfred North Whitehead and Gilbert Simondon, it is intended to rethink the sensible root of aesthetics by extending it to reality as a whole. If every aspect of reality finds its foundation in a “diffuse” feeling, aesthetics can serve as the basis and cosmological synthesis of the encyclopedia of knowledge: the Ruyerian idea of an “survol absolu”, the Whiteheadian concept of “prehension” and the Simondonian conception of cybernetics as an “allagmatic” seem to redefine aesthetics as a true cosmology of contemporaneity.